PERSEPSI GURU-GURU SMKN 5 PADANG TENTANG PENGHAPUSAN UJIAN NASIONAL (UN) - Gefri Hidayat; Revian Body (Teknik Sipil Universitas Negeri Padang, 2021)
This study aims to determine the perceptions of SMKN 5 Padang teachers about the elimination of the national exam (UN). This research is included in descriptive research. This research was aimed at all teachers of SMKN 5 Padang who became teachers in the 2020/2021 academic year, as many as 20 people.All teachers were sampled using the total sampling technique. Data retrieval conducted using a questionnaire and a Likert scale used for the answer scoring system. The number of statement items in the questionnaire was 22 items. The results showed that the perceptions of SMKN 5 Padang teachers about the elimination of the national exam (UN) were in good categories, this was obtained by using the degree of achievement formula, namely: on the UN objective indicator, teachers' perceptions about the UN objectives were 84.17% with the category good; on the indicators of the positive impact of the implementation of the National Examination, teachers' perceptions of the positive impact of the implementation of the National Examination were 84.04% with a good category; on the indicators of the negative impact of the implementation of the National Examination, teachers' perceptions of the negative impact of the implementation of the National Examination were 76.88% with the sufficient category; and on the UN implementation indicators for SMK, the perceptions of teachers about the implementation of the UN for SMK was 88.75% with a good category.